1994
DOI: 10.1002/tea.3660310503
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of natural selection: a snapshot of the sense‐making process

Abstract: Several studies have examined the alternative conceptions that students possess about the process of natural selection. The goal of this study was to explore the nature of the changes in students' explanations of evolutionary scenarios. Fifty names were randomly selected from a pool of over 200 high school students who took a pretest prior to and a posttest following instruction about evolution. Teleological and Lamarckian explanations accounted for over half of the students' explanation on the pretest, but dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
12

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 10 publications
(9 reference statements)
1
66
0
12
Order By: Relevance
“…Much of this work has focused on confusions about the process of natural selection (e.g., Bishop and Anderson 1990;Settlage 1994;Jensen and Finley 1996;Nehm and Reilly 2007). These, and other studies, have identified some widespread misconceptions about principles of natural selection (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this work has focused on confusions about the process of natural selection (e.g., Bishop and Anderson 1990;Settlage 1994;Jensen and Finley 1996;Nehm and Reilly 2007). These, and other studies, have identified some widespread misconceptions about principles of natural selection (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The results of deficient learning are the permanence and diffusion of a great roll of problematic issues about evolution and correlated subjects (for examples, see Bishop & Anderson, 1990;Aleijandre, 1994;Settlage, 1994;Zuzovsky, 1994;Demastes et al, 1995Demastes et al, , 1996Jensen & Finley, 1996;Ferrari & Chi, 1998;Thomas, 2000;Anderson et al, 2002;and Passmore & Stewart, 2002). Concepts such as temporal dimension and its consequences to the evolutionary process are commonly misinterpreted, as well as the genealogical relationships among men and other animals, whether humans originated through purely natural processes from other forms of life, and the difference between evolutionary changes, evolutionary novelties and progress.…”
Section: Resultsmentioning
confidence: 99%
“…This tendency of secondary school students toward biological evolution explanations based on purpose is common and persistent throughout the literature (e.g., Alters & Nelson, 2002;Beardsley, 2004;Bizzo, 1994;Clough & Wood-Robinson, 1985;Deadman & Kelly, 1978;Geraedts & Boersma, 2006;Jensen & Finley, 1996;Jiménez-Aleixandre, 1992;Kampourakis & Zogza, 2008Passmore & Stewart, 2002;Pedersen & Halldén, 1992;Prinou et al, 2008;Samarapungavan & Wiers, 1997;Settlage, 1994;Shtulman, 2006;Southerland et al, 2001;Tamir & Zohar, 1991) and even into postsecondary education (Kelemen & Rosset, 2009). In fact, in a study of university nonmajor biology students, Jensen and Finley (1996) identified the most common misconception responses were related to purposeful evolution.…”
Section: Percent Responsementioning
confidence: 94%
“…Numerous studies conducted in recent decades identify multiple biological evolution-related misconceptions held by select groups of students. These groups include: secondary students (Beardsley, 2004;Bizzo, 1994;Clough & Wood-Robinson, 1985;Creedy, 1993;Deadman & Kelly, 1978;Demastes et al, 1995;Evans, 2000;Geraedts & Boersma, 2006;Halldén, 1988;Jiménez-Aleixandre, 1992;Jungwirth, 1975;Kampourakis & Zogza, 2007, 2008Lawson & Thompson, 1988;Palmer, 1999;Pedersen & Halldén, 1992;Prinou et al, 2008;Settlage, 1994;Shtulman, 2006;Spindler & Doherty, 2009;Tamir & Zohar, 1991); first year undergraduate students (Brumby, 1979;Jensen & Finley, 1995;Nehm & Reilly, 2007;Sundberg & Dini, 1993); second year undergraduate students (Jiménez-Aleixandre & Fernández-Pérez, 1987) collective undergraduate students (Anderson et al, 2002;Bishop & Anderson, 1990;Brem et al, 2002;Chinsamy & Plagányi, 2007;Demastes et al, 1995;Ferrari & Chi, 1998;Hokayem & BouJaoude, 2008;Jensen & Finley, 1996;Meir et al, 2007;Paz-y-Mińo & Espinosa, 2009;Robbins & Roy, 2007;Shtulman, 2006;…”
Section: Introductionmentioning
confidence: 99%